Reflections on the Islamization of Mongol Khans in Comparative Perspective - Jackson, Peter (Journal of the economic and social history of the Orient, 2019)
Abstract This paper compares the process of Islamization in the three westernmost Mongol states: the Chaghadaid Khanate in Central Asia; the Ilkhanate in Iran and Iraq; and the Jochid ulus (the Golden Horde) in the Pontic-Caspian steppes and the Volga region. It explores in greater depth the hallmarks of conversion, the agents of, and the motives for, Islamization and the limitations of its effects on royal policy. In particular, it highlights the tension between Islamic notions and the concept of religious pluralism that was central to the corpus of Mongol law (Yasa) established by Chinggis Khan.